LIVING HADIS DALAM TRADISI MA’GAWE PASCA PERNIKAHAN DI MAKAM DATUK SULAIMAN DESA PATTIMANG KECAMATAN MALANGKE KABUPATEN LUWU UTARA - dan Syarif Hasyim, Amrullah Harun, Nirmayanti, , Ahmad Taqiyuddin, (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
This journal examines the post-wedding Ma'gawe tradition at the grave of Datuk Sulaiman, Pattimang Village, Malangke District, North Luwu Regency. The focus of this study is to determine the meaning of the Ma'gawe tradition for the Pattimang community and its relevance to post-wedding. This research is a type of field research with a descriptive-qualitative method, the approach used is phenomenological. The main primary data sources were obtained through observation, interviews, and documentation from people directly involved in the Ma'gawe tradition after the wedding. Meanwhile, secondary additional data, namely in the form of literature studies, is obtained through books, texts, and journals. Data collection techniques through observation, interviews, and documentation. The results of this research indicate that the community views the Ma'gawe tradition after the wedding at Datuk Sulaiman's grave as a place to ask for blessings from Allah for the marriage they have carried out and as a sense of respect for the people of Pattimang Village for Datuk Sulaiman who has brought Islam to Tana Luwu.